Development of "Lift the Flap" Educational Media on Indonesian Cultural Diversity - Putri, Nizmi; Hidayat, Wahyu; Nadila, Nurhaida (Jurnal Penelitian Medan Agama, 2024)
This research aims to develop learning media in the form of Lift The Flap Book on Indonesian cultural diversity material for students to determine the level of feasibility of media development, as well as determine the level of practicality of the media through teacher responses and after students use Lift The Flap Book media about Indonesian cultural diversity. The research method uses a 4D model with the Research and Development (R&D) method. This research model uses 4 steps, namely Define, Design, Develop, Disseminate. The data collection techniques used were material expert validation questionnaires and media expert validation questionnaires to determine the level of suitability of the media as well as response questionnaires for assessment of class teachers/teachers and students to determine the practicality level of the Flap Book Lift The Media. The research and development subjects were fourth grade students at SD Negeri 105345 Sidodadi Ramunia, Beringin District. The results of research and development produced a design in the form of Lift The Flap Book media to introduce the cultural diversity that exists in Indonesia to fourth grade students at SD Negeri 105345 Sidodadi Ramunia, Beringin District, which received a score of 88.89%, by material experts and received a score of 71.17%. by experts. media. Based on the description above, the product developed by the researcher is suitable for use as a learning medium.